Positive inotropic effects of glucose-dependent insulinotropic polypeptide in the human atrium and the mouse atrium - J. Neumann; B. Hofmann; U. Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Glucose-dependent insulinotropic polypeptide formerly called gastrin inhibitory peptide (GIP), a peptide composed of 42 amino acids, is formed in duodenal and jejunal cells. GIP acts via GIP receptors (GIPR). GIPR can stimulate adenylyl cyclases (AC) and increase intracellular cyclic adenosine-3´,5´-monophosphate (cAMP) levels. The physiological role of GIPR in the human heart is not fully understood. Thence, force of contraction (FOC) was studied in isolated electrically driven (1 Hz) human right atrial preparations from patients undergoing bypass surgery due to severe coronary heart disease. We noted that in paced human atrium, GIP increased FOC. This effect was reduced by a GIPR-antagonist (ProGIP). In the presence of 0.1 µM cilostamide, a phosphodiesterase (PDE) 3 inhibitor, the positive inotropic effects (PIE) of GIP were more potent and efficient to raise FOC. Up to 100 nM GIP failed to heighten the spontaneous beating rate in mouse right atrial preparations, but increased FOC in electrically driven left atrial mouse preparations but only in the presence of a PDE 4 inhibitor (100 nM rolipram). We conclude that the human atrium and the mouse atrium contain functional GIPR with respect to FOC.